SIOBAK CIK KHE LOK: AKULTURASI KULINER BALI DAN TIONGHOA DI KABUPATEN BULELENG (SEJARAH DAN POTENSINYA SEBAGAI MEDIA PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMA) - Suadnyana, Kadek Nova; Arta, Ketut Sedana; Purnawati, Desak Made Oka (Universitas Pendidikan Ganesha, 2024)
This study aims to: (1) to know the background of the establishment of Siobak Cik Khe Lok stall in Buleleng; (2) to know the principles, patterns and marketing strategies of Siobak Cik Khe Lok; and (3) to know the aspects of Siobak Cik Khe Lok that have potential as media for the Pancasila Student Profile Strengthening Project (P5) in high school. The method used in this research is historical research method with qualitative approach. The results of this study show that the establishment of Siobak Cik Khe Lok stalls in Buleleng cannot be separated from the beginning of the arrival of ethnic Chinese in Buleleng. The principles, patterns and strategies used by Siobak Khe Lok so that it can stand until now are generation to generation by passing down recipes to children and grandchildren. The potential of Siobak Cik Khe Lok can be used as a media source for the Pancasila Student Profile Strengthening Project (P5) in high school because Siobak Cik Khe Lok contains a long history that includes local history. This can be related to the theme in P5, namely Local Wisdom. In addition, students will adopt marketing knowledge from Siobak Cik Khe Lok which is implemented in the school bazaar. Keywords: History, Siobak, P5, marketing.